Development of a cereal bar with the addition of sweet potato flour, collagen and betaine: review of the ingredients used and feasibility (Research, Society and Development, 2022)
The development of new products for the food industry is increasingly necessary, even in an increasingly competitive market that seeks to meet the demands of demanding consumers. The cereal bar serves an audience that seeks versatility and health benefits, due to its high nutritional value. The formulation with sweet potato, betaine and collagen seeks to meet the requirements to introduce on the market an innovative product with vast nutrients, such as complex carbohydrates, proteins, amino acids, vitamin A, vitamins B and mineral salts. The present study aims to provide a deep understanding of the development of a new cereal bar formulation, reviewing all the ingredients used, in addition to the importance of market analysis as a strategy for evaluating and developing new food products.